Short-term outcome of newborn infants: spinal versus general anesthesia for elective cesarean section - A prospective randomized study - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 2001)
Objective: To compare general and spinal anesthesia with respect to the short-term outcome of newborns born by elective cesarean deliveries. Methods: Pregnant women admitted to our hospital from January 1999 to July 2000, for whom elective repeat cesareans were planned after 37 weeks gestation. were allocated randomly after their informed consent to spinal anesthesia or general anesthesia. Maternal age. gestational age. birth weight. Apgar's score, hospital stay duration, and duration of cesarean section time were all noted. The rate of the neonatal respiratory depression, perinatal asphyxia, and admittance to the neonatal intensive care unit of the infants were documented. We also studied arterial samples withdrawn from the cord for the pH, bicarbonate, PaO2 (oxygen pressure, arterial), and PaCO2 (carbon dioxide pressure, arterial). The serum levels of creatine kinase with myocardial-specific isoform, aspartate aminotransferase, alanine aminotransferase, and total cortisol levels of the newborns were measured and served in ruling out perinatal stress and in confirming the diagnosis of perinatal asphyxia (and of myocardial damage). Statistical analyses was performed,vith the use of an unpaired Student's t-test, Chi-square test, and a power calculation was done. Results: From the randomly selected patients, we had 38 (45.2%) infants for general anesthesia and 46 (54.8%) for spinal anesthesia. None of our primary endpoints favored any of the Study groups, and the clinical short-term outcome of the infants was similar in the neonates born both by spinal and general anesthesia (P>0.05). The biochemical assays did not rule out or confirm any differences in the occurrence of perinatal stress (P>0.05). Conclusion: Anesthesia type does not seem to influence the short-term outcome of the newborn infants for the elective cesarean deliveries. We believe that both spinal and general anesthesia could be performed in elective term cesarean deliveries without any risk to the newborn infants. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: anesthesia; cesarean; neonatal outcome; REGIONAL ANESTHESIA; FETAL ACIDEMIA; APGAR SCORE; DELIVERY; ASPHYXIA